Están con nosotros o con los terroristas El efecto Al Qaeda y la Guerra de Iraq en América Latina - Montaner, Gonzalo (Ariadna Ediciones, 2020)
The book studies the relations between Latin America and the US Government from 11S and the potential influence of Islamic terrorism in the region; the different reactions of local governments and the pressures developed by the State Department for Latin America to adopt a unique policy in favor of the White House